Personnel Records Management In Tanzania - Andrew Malekani; Christian Mubofu (Record and Library Journal, 2023)
Background of the study: Inadequate and improper storage facilities, absence of electronic records management system, inadequate space for records storage, human resource officer’s lack of records management skills and lack of internal training were the main challenges affecting the management of personnel records in Liwale district council. Purpose: The study aimed at investigating the personnel records and the challenges faced in management of these records in Liwale district council (LDC) in Tanzania. Method: The study used a qualitative approach in which 30 respondents were purposely selected. Questionnaires and in-depth interviews were used to collect data. Quantitative data were analyzed using Statistical Package for Social Science version 20 while qualitative data were subjected to content analysis. Findings: Findings revealed that appointment letters and letters of confirmation were the most cited (16.7%) type of personnel records readily available in various departments at Liwale District Council. Others include health and social security records, letter of transfer, notification of termination/death and retirement, medical report, wages and salary slip, and copy of birth certificate. Conclusion: It is recommended that Liwale district council should address the challenges faced in the management of personnel records for better and fair decision-making.